2017
DOI: 10.1111/eci.12852
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular mechanics after repair of subarterial and perimembranous VSDs

Abstract: Adolescents and adults late after repair of subarterial and perimembranous VSDs show impairment of RV systolic and diastolic myocardial deformation. The RV outflow function and LV systolic deformation appear to be worse after repair of subarterial defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Although this research demonstrated they have reduced myocardial strain, Ross and Ross Konno procedures have good long term results with a low incidence of heart failure (22). Numerous studies have demonstrated abnormal strain in a range of CHD populations, including ventricular septal defects (23), tetralogy of Fallot (12), and transposition of the great arteries (24), however the clinical significance of these findings is not always clear. In a heterogeneous adult population reduced GLS is an independent prognostic predictor of major adverse cardiac events, stronger even than LVEF (8), however whether this remains true in the Ross and Ross-Konno groups is yet to be explored.…”
Section: Editorial Commentarymentioning
confidence: 90%
“…Although this research demonstrated they have reduced myocardial strain, Ross and Ross Konno procedures have good long term results with a low incidence of heart failure (22). Numerous studies have demonstrated abnormal strain in a range of CHD populations, including ventricular septal defects (23), tetralogy of Fallot (12), and transposition of the great arteries (24), however the clinical significance of these findings is not always clear. In a heterogeneous adult population reduced GLS is an independent prognostic predictor of major adverse cardiac events, stronger even than LVEF (8), however whether this remains true in the Ross and Ross-Konno groups is yet to be explored.…”
Section: Editorial Commentarymentioning
confidence: 90%
“…This type of dysfunction has received little attention ( 70 ). Interestingly, patients with isolated VSD show signs of impaired RV function late after VSD closure, but to what extent the IVS contributes to this dysfunction has yet to be determined ( 71 , 72 ).…”
Section: The Phenotype Of Right Ventricular Dysfunctionmentioning
confidence: 99%